YouTube as a Source of Educational Content in Teenagers' Learning Practices - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 9th European Conference on Social Media, 2022)
YouTube is one of the most popular online social spaces nowadays combining features of both a huge repository of information and a social networking service. Millions of people use this video-sharing platform daily. Entertainment (sports, comedy, music, movie trailers), information seeking (missed news, product reviews, research on a specific topic), and educational purposes (how-to videos, learning math, or tactics for video games) were discussed as main motivational aspects for watching YouTube videos (Lagger et al. 2017). Usage of YouTube for educational purposes became particularly relevant for teenagers as a support for their home-schooling. Our goal is to find out what strategies teenagers use to find relevant educational content on the service and how important this content was for their everyday learning practices before and during the COVID pandemic. We analyzed online behavior of 34, 14 to 15-year old teenagers (47% male) who took part in a long-term adventure trip with digital media left aside. We gathered quantitative data seven months before the trip (March 2019), just before the trip (October 2019), on the last day of the trip (April 2020), and five months after the trip (September 2020). We also conducted in-depth interviews with nine teenagers, who named YouTube as their favourite online service. Our intention is now to conduct nine additional interviews with the same teenagers to see whether their everyday learning practices changed within the last year. Implications drawn from this study, further research perspectives, and limitations will be presented and discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: educational benefits of YouTube; online learning; social media overuse; teenage usage of social networks; YouTube usage patterns